Loss and xenophobia in the city: contextualizing anti-Syrian sentiments in Izmir, Turkey - Saraçoğlu, Cenk; Bélanger, Danièle (Patterns of prejudice, 2019)
Many research reports and scholarly articles based on survey data show that public opinion in Turkey towards Syrians has become more negative in recent years. Based on ethnographic fieldwork conducted in four research sites in Izmir, Saraçoğlu and Bélanger show that anxiety about losing a preconceived notion of status is constitutive of the local Turkish population's attitudes towards the inflow of Syrian refugees. The perception of loss that frames xenophobic attitudes against the Syrians appears in three different but related forms: (1) loss of economic gains; (2) loss of urban space; and (3) loss of national cohesion. By focusing on the ways in which this sense of loss is constructed in urban social relations, Saraçoğlu and Bélanger aim to unpack some embedded political, ideological and economic conditions that provide fertile ground for the formation of anti-Syrian xenophobia. Their analysis contributes to and goes beyond the relevant literature that descriptively demonstrates the extent to which anti-Syrian xenophobia is prevalent across Turkey.